Symptomatic Intrathecal Hematoma following an Epidural Blood Patch for an Obstetric Patient with Postdural Puncture Headache: A Case Report and Synthesis of the Literature. (18th March 2020) - McInerney, Hailey J.; Lee, Manuel; Saunders, Tracie; Schabel, Joy; Adsumelli, Rishimani S. N.
Abstract : Epidural blood patch (EBP), generally considered a low-risk procedure, can potentially lead to significant neurological complications. We report the case of a parturient who underwent an uneventful EBP for postdural puncture headache (PDPH) and subsequently presented with progressively worsening radicular symptoms. Magnetic resonance imaging (MRI) revealed an intrathecal hematoma, and conservative management with steroids led to complete recovery. Our case highlights the possibility of this rare complication following an uneventful procedure and the importance of prompt diagnosis and treatment to prevent serious adverse outcomes. Literature review, EBP alternatives, and strategies to minimize complications following blood patch will be discussed in this report.